Tradisi Tama Maus Sonaf Bana sebagai Sumber Pembelajaran Sejarah Lokal - Yuditha Sofiana Kofi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
History learning based on local history makes a significant contribution to students' learning development because the learning process becomes more varied and enjoyable. The Tama Maus tradition among the Bana Bikomi people can be a part of local history used in the history learning process at school. In this study the author analyzes the Tama Maus tradition as learning material based on local history, which can introduce various knowledge about life during the kingdoms in Indonesia as depicted in the process of implementing the Tama Maus tradition.